Axial compression behavior of stub square bimetallic steel tubes. (December 2021) - Li, Hongda; Jia, Chen; Guo, Lanhui; Huang, Haijia
Abstract: In this paper, the axial compression behavior of the stub square bimetallic steel tube was investigated through experiments and finite element analysis. Firstly, a total of twelve specimens were fabricated and subjected to axially compressive loads, and the experimental parameters contained the section type (hollow section or concrete-infilled section) and the breadth-to-thickness ratio. The test results indicated that the ultimate resistance of the bimetallic steel tubes decreased obviously with the increase of breadth-to-thickness ratio due to the early onset of local buckling. Besides, the internal concrete effectively prevented the inward buckling of the steel tube, therefore the ultimate resistance of the concrete-infilled tube was higher than that of the hollow tube, and the improvement increased with the increase of the breadth-to-thickness ratio. Then the finite element models were built and verified by experimental results. The parametric analysis was conducted and three parameters, including the breadth-to-thickness ratio, the percentage of the stainless steel content and the yield strength of the carbon steel, were considered. Finally, the critical breadth-to-thickness ratio of hollow and infilled steel tubes was discussed. The results revealed that the values regulated in AISC 360-16, EN 1993-1-1 and GB 50017-2017 were unsafe for the bimetallic steel tubes with hollow sections, and the values in AISC 360-16 and CECS 159: 2004 were also unsafe for the bimetallic steel tubes filled with concrete. Graphicl abstract: Unlabelled Image Highlights: The buckling behavior of the stub square bimetallic steel tubes was investigated through experiments and FE analysis. The critical breadth-to-thickness ratios provided by different design codes have been discussed. An equation for determining the peak resistance of bimetallic steel tubes filled with concrete has been suggested.